Platelets loaded with liposome‐encapsulated thrombin have increased coagulability. (20th April 2018) - Chan, V.; Sarkari, M.; Sunderland, R.; St. John, A. E.; White, N. J.; Kastrup, C. J.
Abstract : Essentials Platelet transfusions can have limited efficacy during hemorrhage associated with coagulopathy. Thrombin can be shielded by encapsulation into nanoliposomes and delivered to platelets ex vivo . Loading platelets with liposomal thrombin improved several aspects of platelet coagulability. Platelets loaded with liposomal thrombin can overcome some coagulopathic deficiencies in vitro . Summary: Background: Platelets are integral to clot formation and are often transfused to stop or prevent bleeding. However, transfusions of platelets are not always effective, particularly in the most severe cases of hemorrhage. Nanoparticle systems have been developed to mimic platelets but inherently lack important aspects of platelet function, which limits their potential effectiveness. Objectives: Increasing the natural coagulability of transfusable platelets could increase their efficacy during treatment of severe hemorrhage. Thrombin is a potent platelet agonist that currently cannot be used intravenously because of the risk of thrombosis. We hypothesized that delivery of thrombin to ex vivo platelets via liposomal encapsulation would enable transfusable platelets to become more coagulable in response to platelet agonists. Methods: Thrombin was encapsulated into nanoliposomes and delivered to platelets ex vivo . Platelet coagulability was measured by monitoring platelet activation, clot contraction, clot time and clot stability in several in vitro assays. These parameters were also measured under conditions where coagulation is compromised, including during acidosis, antiplatelet drugs, hemophilia A and trauma‐induced coagulopathy. Results: Liposomal thrombin was endocytosed and used by platelets ex vivo but was not secreted upon activation. These modified platelets became more sensitive and responsive to agonists and improved clotting time even under conditions that normally cause platelet dysfunction or have impaired coagulation. Conclusions: Several aspects of platelet function were enhanced by ex vivo delivery of liposomal thrombin.